Study of the Bespakyr Mazar and assessment of cultural heritage deterioration using digital technologies - Minibulatovna, Mukhamadeyeva, Railya; Aleksandrovna, Mukhamadeyeva, Irina; Elmeslehi, Alkafafi, Ahmed Taufik (International Journal of Innovative Research and Scientific Studies, 2025)
The preservation and study of cultural and historical heritage is a multidimensional issue, encompassing aspects of sociology, politics, economics, and environmental science. This research focuses on the Bespakyr Mazar, a significant cultural heritage site in Northern Kazakhstan, and presents a digital approach to assessing its structural degradation. The study explores the historical significance of mazars, their role in Kazakh culture, and their function in preserving ancestral memory. A methodology for assessing the deterioration of historical structures using digital technologies is proposed. This approach integrates three-dimensional (3D) modeling, comparative analysis of past and present photographic evidence, and metrological instruments. The proposed method enables precise monitoring of wear and structural damage over time, offering an effective solution for heritage conservation efforts. Furthermore, the study advocates for immersive digital environments that allow for interactive exploration of cultural heritage sites, making them accessible to researchers, educators, and the general public.